INOVASI MANAJEMEN PERPUSTAKAAN DALAM RANGKA MENDUKUNG BUDAYA LITERASI SEKOLAH - Tri Widodo; Mulyanto; Rahmat Mulyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this study is to describe library management innovations in order to support a culture of school literacy at SMP Negeri 31 Purworejo. The specific objective of this study was to determine the effectiveness of library management at SMP Negeri 31 Purworejo between the manual system compared to the use of applications seen from the national library management standard. This type of research is quasi-experimental research, conducted to determine the effect of a treatment on the characteristics of the subjects studied. In quasi-experimental research it is not possible to control all relevant variables. The subjects of this study were librarians, principals, teachers and students. Data collection was carried out through questionnaires, interviews, observation and documentation. The analysis technique in this study is the percentage technique. To determine the descriptive type of the percentage obtained by each indicator in the variable, and the percentage descriptive calculation is then interpreted into sentences. In this study, percentage data will be obtained before using the application and data after using the application. The size of the percentage will determine the effectiveness of library service management between the manual system and the application. The results of this study indicate that: the use of library applications is more effective in management innovation to support school literacy culture is acceptable. This is evidenced by the results of data analysis where the average score for library management at SMP Negeri 31 Purworejo (manual) was 61.40% and SMP Negeri 9 Purworejo (application) was 65.46%. As for students' reading interest, SMP Negeri 31 Purworejo (manual) has an average score of 65.28 while SMP Negeri 9 Purworejo (application) is 69.88. With the results of this analysis it is clear that the proposed hypothesis can be accepted.